Revitalization of the 1970s within the "Old Town" in Kraków = Rewitalizacja zabudowań z lat 70. XX wieku w obrębie Starego Miasta w Krakowie - Żwirek, Paweł; Fiszer, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents selected issues in the revitalization of the façades of buildings located in the historic ?Old Town? part of the city of Kraków. The subjects of the revitalization were the façades of an office building and a multi-level garage, both built in the 1970s in the administrative district of the "Old Town" in Krakow.
Keywords: budynek biurowy; rewitalizacja; fasada budynku; aluminium; elewacja wentylowana; siatka cięto-ciągniona; office building; revitalisation; façade of building; ventilated facade; expanded metal